A Systematic Umbrella Review on the Epidemiology of Modifiable Health Influencing Factors and on Health Promoting Interventions Among University Students - Pavel Dietz; Jennifer L. Reichel; Dennis Edelmann; Antonia M. Werner; Ana Nanette Tibubos; Markus Schäfer; Perikles Simon; Stephan Letzel; Daniel Pfirrmann (Frontiers Media S.A., 2020)
Background: Universities represent an important setting for health promotion. The unique collective of university students is of particular relevance since they are the leaders, decision-makers, and parents of tomorrow. In this context, modifiable health influencing factors as well as interventions to prevent these, play a crucial role. Therefore, the present umbrella review aims to (i) provide an overview of review articles addressing epidemiological issues (prevalence and determinants) of modifiable health influencing factors in university students and (ii) to provide an overview of review articles addressing the evidence of interventions to promote/enhance modifiable health influencing factors in university students.Methods: A systematic literature search was performed in the databases PubMed, Cochrane Reviews Library und Web of Science according to the PRISMA guidelines. Only systematic reviews and meta-analyses were included. The AMSTAR-2-Tool was used for the quality assessment.Result: The initial search resulted in 10,726 records of which 81 fulfilled the inclusion criteria, with a further distinction in articles with an epidemiological focus (n = 39) and in articles with interventional approaches (n = 42). Topics of the different review articles ranged from physical activity over mental health, substance use, sleep, diet and nutrition, and media consumption. Many review articles had a specific focus on medical and nursing students and originated from the U.S.A., U.K., or China.Discussion: This umbrella review provides an overview of review articles on the epidemiology of modifiable health influencing factors and on the evidence of interventions targeting these factors among university students. Thereby, experts as well as stakeholders in the field could gain insights into crucial target points for health promotion. It identifies research gaps in terms of study region and groups of students.